Oral and Maxillofacial Surgery 2021
DOI: 10.5772/intechopen.93223
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Temporal Bone

Abstract: Numerous neurological lesions and tumors of the paranasal sinuses and oral cavity may spread into the middle and posterior cranial fossae through the anatomical apertures. For the appropriate management of these pathologies, many extensive surgical approaches with a comprehensive overview of the anatomical landmarks are required from the maxillofacial surgery's point of view. The surgical significance lies in the fact that iatrogenic injury to the petrous segment of the temporal bone including the carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…This can be explained by the normal development of the mastoid processes, which are absent at birth but undergo rapid growth during the first year of life. [25][26][27] Furthermore, the most inconsistent measurement was FT due to the difficulty in defining the chin point, which led to inconclusive results. Contrary to Ploplys et al, 4 who described the chin point as always pointing away from the closed suture, the chin points of patients in the present study varied greatly from pointing away from or toward the closed suture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the normal development of the mastoid processes, which are absent at birth but undergo rapid growth during the first year of life. [25][26][27] Furthermore, the most inconsistent measurement was FT due to the difficulty in defining the chin point, which led to inconclusive results. Contrary to Ploplys et al, 4 who described the chin point as always pointing away from the closed suture, the chin points of patients in the present study varied greatly from pointing away from or toward the closed suture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mastoid processes were not always present (especially on the preoperative scans), which could lead to inconclusive results regarding the change in SBC. This can be explained by the normal development of the mastoid processes, which are absent at birth but undergo rapid growth during the first year of life 25–27 . Furthermore, the most inconsistent measurement was FT due to the difficulty in defining the chin point, which led to inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding skull base cant, because of the natural development of the mastoid processes, which are absent at birth but grow rapidly during the first year, the extent of ACFC was sometimes hard to calculate, especially using preoperative CT scans. [41][42][43] Moreover, given that these measurements represent visual estimates and are subsequently prone to inconsistencies, a potential compensation could involve several observers performing the same measurements. However, ICC analysis showed that the variability within the same patient was much lower than that between patients, suggesting the reproducibility of the measurements and the adequacy of the previously defined reference points used for the measurements.…”
Section: Plastic and Reconstructive Surgery • February 2024mentioning
confidence: 99%
“…Bu iki yapının uçlarını birleştiren hayali bir çizgi üçgeni tamamlar. Suprameatal üçgenin üst sınırını (üst kenarını) oluşturan suprameatal tepe, fossa cranii media tabanını ve bu noktada yer alan dura mater cranialis'in açılanmasını temsil etmektedir (1)(2)(3)(4). Linea temporalis, fossa cranii media'da dura mater'in hemen altında ve cellulae mastoideae üzerinde kemikli bir plaka olan tegmen tympani'ye karşılık gelmektedir.…”
Section: Introductionunclassified
“…Suprameatal (Macewen) üçgendeki kribriform alanı, antrum mastoideum mukozasının damarları için bir geçit görevi gören çok sayıda küçük foramenle delinmiştir. Bu nedenle üçgenin kenarlarındaki diseksiyon nörovasküler yapıların olmaması nedeniyle daha güvenli görülmektedir (1,6). Suprameatal çıkıntının temel işlevi cartilago auricularis'lerin yani kulak kıkırdaklarının tutunma yerini oluşturmaktır (8).…”
Section: Introductionunclassified